Common Statin Intolerance Variants in ABCB1 and LILRB5 Show Synergistic Effects on Statin Response: An Observational Study Using Electronic Health Records - Melhem, Alaa’ Lutfi; Chourasia, Mehul Kumar; Bigossi, Margherita; Maroteau, Cyrielle; Taylor, Alasdair; Pola, Roberto; Dawed, Adem Y.; Tornio, Aleksi; Palmer, Colin N. A.; Siddiqui, Moneeza K. (Frontiers in Genetics, 2021)
Background Statin intolerance impacts approximately 10% of statin users, with side effects ranging from mild myalgia to extreme intolerance resulting in myopathy and rhabdomyolysis. Statin intolerance results in poor adherence to therapy and can impact statin efficacy. Many genetic variants are associated with statin intolerance. The effect of these variants on statin efficacy has not been systematically explored. Methods Using longitudinal electronic health records and genetic biobank data from Tayside, Scotland, we examined the effect of seven genetic variants with previously reported associations with simvastatin or atorvastatin intolerance on the outcome of statin response. Statin response was measured by the reduction achieved when comparing pre-and post-statin non-HDL-cholesterol. Post-treatment statin response was limited to non-HDL-cholesterol measured within six months of therapy initiation. Univariate and multivariable linear regression models were used to assess the main and adjusted effect of the variants on statin efficacy. Results 9,401 statin users met study inclusion criteria, of whom 8,843 were first prescribed simvastatin or atorvastatin. The average difference in post-treatment compared to pre-treatment non-HDL-cholesterol was 1.45 (±1.04) mmol/L. In adjusted analyses, only two variants, one in the gene ABCB1 (rs1045642) and one in LILRB5 (rs12975366), were associated with statin efficacy. In ABCB1, homozygous carriers of the C allele at rs1045642 had 0.06 mmol/L better absolute reduction in non-HDL-cholesterol than carriers of the T allele (95%CI: 0.01,0.1). In LILRB5 (rs12975366), carriers of the C allele had 0.04 mmol/L better absolute reduction compared to those homozygous for the T allele (95%CI: 0.004,0.08). When combined into a two-variant risk score, individuals with both the rs1045642-CC genotype and the rs12975366 -TC or CC genotype had a 0.11 mmol/L greater absolute reduction in non-HDL-cholesterol compared to those with rs1045642-TC or TT genotype and the rs12975366 -TT genotype (95%CI: 0.05, 0.16; P<0.001). Conclusions We report two genetic variants for statin adverse drug reactions that are associated with statin efficacy. While the ABCB1 variant has been shown to have an association with statin pharmacokinetics, no similar evidence for LILRB5 has been reported. These findings highlight the value of genetic testing to deliver precision therapeutics to statin users.